1994
DOI: 10.1002/ijc.2910570226
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of recombinant human Cu, Zn‐superoxide dismutase on lung metastasis of murtne tumor cells

Abstract: The inhibitory effect of recombinant human Cu++Zn++superoxide dismutase (rhSOD) on metastasis of tumor cells in the mouse was investigated. In an experimental pulmonary metastasis model employing Meth A cells as inoculum, significant inhibition of metastasis was obtained by intravenous pre- and post-administration of rhSOD. An inhibitory effect of rhSOD was also observed in a spontaneous pulmonary metastasis model with 3LL cells as the inoculum. rhSOD was not observed to have any significant effects on the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 13 publications
0
28
0
1
Order By: Relevance
“…[4][5][6] Oxygen radicals are produced not only by inflammatory cells such as activated neutrophil and macrophage infiltrating tumor foci, but also tumor cells. 7 We and others have reported that oxygen radicals enhance metastasis in various organs such as lung, 8 liver 9 and bone. 10 We then revealed the fact that superoxide (O − 2 ), a representative oxygen radical, provokes tumor cell motility and invasion as a mechanism by which oxygen radicals promote metastasis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[4][5][6] Oxygen radicals are produced not only by inflammatory cells such as activated neutrophil and macrophage infiltrating tumor foci, but also tumor cells. 7 We and others have reported that oxygen radicals enhance metastasis in various organs such as lung, 8 liver 9 and bone. 10 We then revealed the fact that superoxide (O − 2 ), a representative oxygen radical, provokes tumor cell motility and invasion as a mechanism by which oxygen radicals promote metastasis.…”
Section: Introductionmentioning
confidence: 97%
“…We also reported the anti-metastatic activity of SOD in both experimental and spontaneous metastatic models with results compatible with the above findings. 8 Takenaga et al 13 confirmed the anti-metastatic effect of SOD and perceived that tumor cell injection caused rapid infiltration of inflammatory cells and excessive free radical production in mouse lung. These facts endorsed the effectivenesss of SOD against metastasis.…”
Section: Introductionmentioning
confidence: 97%
“…It has also been shown that overexpression of MnSOD suppresses the malignant phenotype of human breast cancer cells (Li et al, 1995) and the metastasis of mouse ®brosarcoma cells (Saord et al, 1994) and potentiated cell dierentiation caused by a dierentiating reagent . Moreover, copper-zinc SOD (CuZnSOD) can induce dierentiation of erythroleukemia cells (Beckman et al, 1989), suppress the metastasis of mouse ®brosarcoma cells (Yoshizaki et al, 1994), and control the motility and invasiveness of human tongue carcinoma cells (Muramatsu et al, 1995). CuZnSOD is found primarily in the cytoplasm and thus it appears that both forms of SOD, which are found in two dierent cellular locations, have a tumor suppressive eect.…”
Section: Introductionmentioning
confidence: 99%
“…All the techniques have been reported to reverse malignant phenotypes of tumour cells. They are (i) intravenous or subcutaneous administration of recombinant human SOD which substitutes specific amino acid for stable one (Yoshizaki et al, 1994); (ii) intravenous administration of SOD conjugated with a pyran copolymer, for prolongation of its activity (Oda et al, 1989); (iii) addition of exogenous liposomal SOD (Beckman et al, 1988); (iv) intraperiponeal or subcutaneous administration of a selective SOD mimetic molecule of nonpeptidic and low molecular weight (Samlowski et al, 2003); (v) elevation of SOD level by sense cDNA transfection (Safford et al, 1994); (vi) inoculation of fibroblasts that are genetically modified to secrete SOD (Tanaka et al, 2001); (vii) elevation of SOD levels by exposure to a superoxide generator and subsequent isolation of superoxide-resistant cells (FernandezPol et al, 1982); (viii) secondary induction of SOD in tumour ) every day from 2 days before coimplantation to the end of the experiment. All the mice were killed under ether anaesthesia at 28 days after implantation, and serum and tumour tissues were collected for examination.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that tumour cells tend to have reduced activities of those SODs compared to normal counterpart (Sykes et al, 1978;Oberley and Buettner, 1979;St Clair and Holland, 1991;Brorrello et al, 1993), and overexpression of SOD decreases malignant phenotypes in various cancers including breast cancer (Li et al, 1995), melanoma (Chruch et al, 1993) and glioma (Zhong et al, 1997). Moreover, it is known that levels of SODs inversely correlate with metastatic ability of tumour cells (Kwee et al, 1991), and that SOD suppresses metastasis of tumour cells in vivo (Safford et al, 1994;Yoshizaki et al, 1994) and inhibits their motility and invasiveness (Muramatsu et al, 1995). Superoxide dismutase also acts as differentiation inducer for erythroleukaemia cells (Beckman et al, 1989).…”
mentioning
confidence: 99%